Effect of Acupuncture on Pain and Quality of Life in Patients with Lumbar Spinal Stenosis: A Case Series Study - Mohammad J. Hadianfard; Ali Aminlari; Arghavan Daneshian; Ali R. Safarpour (Medical Association of Pharmacopuncture Institute, 2016)
Lumbar spinal stenosis (LSS) is a major cause of debilitation in adults, and acupuncture is a recommended treatment. We assessed the effect of acupuncture on pain and quality of life in patients with LSS. Twenty-four patients with LSS who had symptoms of neurogenic claudication were randomly selected and underwent 10 sessions of acupuncture. Pain and quality of life were evaluated before and immediately after the intervention and 6 weeks later using a visual analogue scale and Short Form-36 Health Survey. Paired t tests and repeated measure tests were used to analyze the data. The mean age of the patients was 48.2 ± 10.8 years. The mean visual analogue scale scores before and immediately after intervention (7.9 ± 1.3 and 4.3 ± 2.1) were statistically different (p < 0.001), as was the mean score (3.08 ± 2.3) 6 weeks later (p = 0.01). Five aspects of the Short Form-36 Health Survey score were associated with significant improvements immediately after acupuncture (p < 0.05). Comparisons of the scores before and 6 weeks after intervention showed significant improvements in emotions, vitality, general health, bodily pain, and physical well-being. Therefore, acupuncture had a significant short-term effect on pain and quality of life in patients with LSS.